2022
DOI: 10.1371/journal.pone.0269721
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of azole antifungal resistance in clinical isolates of Candida tropicalis

Abstract: This study was designed to understand the molecular mechanisms of azole resistance in Candida tropicalis using genetic and bioinformatics approaches. Thirty-two azole-resistant and 10 azole-susceptible (S) clinical isolates of C. tropicalis were subjected to mutation analysis of the azole target genes including ERG11. Inducible expression analysis of 17 other genes potentially associated with azole resistance was also evaluated. Homology modeling and molecular docking analysis were performed to study the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…However, we found a higher level of expression of the CDR1 gene in the R-WOM isolates. A recent study also revealed the role of the Tac1, which regulates the overexpression of the CDR1 gene [ 38 ]. However, further investigations are needed to study the precise function of the other efflux pump genes such as CDR2 and CDR3 genes in azole-resistant C. tropicalis from our institute [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, we found a higher level of expression of the CDR1 gene in the R-WOM isolates. A recent study also revealed the role of the Tac1, which regulates the overexpression of the CDR1 gene [ 38 ]. However, further investigations are needed to study the precise function of the other efflux pump genes such as CDR2 and CDR3 genes in azole-resistant C. tropicalis from our institute [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Y132F mutation is responsible for the loss of the normal hydrogen bonding between tyrosine and heme. This alteration affects drug binding because heme is a binding cofactor of azole for ERG11 [ 35 , 36 , 37 ]. Substitutions of both Y132F and S154F prevented the development of Pi-Pi and Pi-cation interactions between the cofactor and the ligand molecules, which lowers the overall binding energy of the altered docked complex [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, antifungal resistance to FCZ has been reported in Candida species from tropical freshwater environments in Brazil and China [ 9 , 53 , 54 , 55 ]. The presence of environmental yeasts with high resistance to FCZ is probably due to the fact that this azole is the most widely used antifungal in humans and animals, and it is among the most reported drugs in hospital and home wastewater [ 56 , 57 ]. In addition, there are fungicides routinely used in agriculture that share the action mechanism of azoles, which can generate cross-resistance in yeasts found in these aquatic environments [ 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of environmental yeasts with high resistance to FCZ is probably due to the fact that this azole is the most widely used antifungal in humans and animals, and it is among the most reported drugs in hospital and home wastewater [ 56 , 57 ]. In addition, there are fungicides routinely used in agriculture that share the action mechanism of azoles, which can generate cross-resistance in yeasts found in these aquatic environments [ 56 , 57 , 58 ]. In Asia, some studies reported a significant increase in resistant C. tropicalis isolated from poultry, and this has been associated with the extensive use of azoles in agriculture [ 56 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation